Plasma exchange for COVID‐19 thrombo‐inflammatory disease. Issue 1 (30th November 2020) - Arulkumaran, Nishkantha; Thomas, Mari; Brealey, David; Alwan, Ferras; Singh, Deepak; Lunn, Michael; Welch, Anna; Clark, Samuel; Raith, Eamon; Reddy, Ugan; Low, Ryan; Leverett, David; et al.
Abstract: Severe COVID‐19 disease is a hyperinflammatory, pro‐thrombotic state. We undertook plasma exchange (PEX) to determine its effects on organ function and thrombo‐inflammatory markers. Seven critically ill adults with severe COVID‐19 respiratory failure (PaO2 :FiO2 ratio < 200 mm Hg) requiring invasive or noninvasive ventilatory support and elevated thrombo‐inflammatory markers (LDH >800 IU/L and D‐dimer >1000 μg/L (or doubling from baseline) received PEX, daily, for a minimum of 5 days. No other immunomodulatory medications were initiated during this period. Seven patients matched for age and baseline biochemistry were a comparator group. Coagulation screening revealed no evidence of coagulopathy. However, von Willebrand Factor (VWF) activity, antigen and VWF antigen: ADAMTS13 ratio, Factor VIII and D‐dimers were all elevated. Following 5 days of PEX, plasma levels of all the above, and ferritin levels, were significantly reduced ( P < .05) while lymphocyte counts normalized ( P < .05). The Pa O2 :FiO2 ratio increased from a median interquartile range (IQR) of 11.6 (10.8‐19.7) kPa to 18.1 (16.0‐25.9) kPa ( P < .05). Similar improvements were not observed in controls. Acute kidney injury (AKI) occurred among five patients in the control arm but not in patients receiving PEX. PEX improved oxygenation, decreased the incidence of AKI, normalized lymphocyte counts and reduced circulating thrombo‐inflammatory markers including D‐Dimer and VWF Ag:ADAMTS13 ratio.